Agreement between Spain and Ecuador regarding the regulation and management of migratory flows - del Reino de España, Gobierno (2016)
The Government of the Kingdom of Spain and the Government of the Republic of Ecuador, hereinafter referred to as Contracting Parties. Encouraged by their common desire to reaffirm their special historical and cultural ties through the fluid and permanent contact of their populations, on the basis of the Agreement of Dual Nationality between both States of March 4, 1964, modified by Protocol of August 25, 1995 , the Agreement on suppression of visas of October of 1963, and the Agreement on Social Security of 1960.